A comparable efficacy and safety between intracardiac echocardiography and transesophageal echocardiography for percutaneous left atrial appendage occlusion - Zhi-Yuan Zhang; Feng Li; Jie Zhang; Lei Zhang; Huan-Huan Liu; Ning Zhao; Fan Yang; Qi Kong; Yi-Ting Zhou; Ling-Ling Qian; Ru-Xing Wang (Frontiers in Cardiovascular Medicine, 2023)
BackgroundAccumulated clinical studies utilized intracardiac echocardiography (ICE) to guide percutaneous left atrial appendage occlusion (LAAO). However, its procedural success and safety compared to traditional transesophageal echocardiography (TEE) remained elusive. Therefore, we performed a meta-analysis to compare efficacy and safety of ICE and TEE for LAAO.MethodsWe screened studies from four online databases (including the Cochrane Library, Embase, PubMed, and Web of Science) from their inception to 1 December 2022. We used a random or fixed-effect model to synthesize the clinical outcomes and conducted a subgroup analysis to identify the potential confounding factors.ResultsA total of twenty eligible studies with 3,610 atrial fibrillation (AF) patients (1,564 patients for ICE and 2,046 patients for TEE) were enrolled. Compared with TEE group, there was no significant difference in procedural success rate [risk ratio (RR) = 1.01; P = 0.171], total procedural time [weighted mean difference (WMD) = −5.58; P = 0.292], contrast volume (WMD = −2.61; P = 0.595), fluoroscopic time (WMD = −0.34; P = 0.705; I2 = 82.80%), procedural complications (RR = 0.82; P = 0.261), and long-term adverse events (RR = 0.86; P = 0.329) in the ICE group. Subgroup analysis revealed that ICE group might be associated with the reduction of contrast use and fluoroscopic time in the hypertension proportion <90 subgroup, with lower total procedure time, contrast volume, and the fluoroscopic time in device type subgroup with multi-seal mechanism, and with the lower contrast use in paroxysmal AF (PAF) proportion ≤50 subgroup. Whereas, ICE group might increase the total procedure time in PAF proportion >50 subgroup and contrast use in multi-center subgroup, respectively.ConclusionOur study suggests that ICE may have comparable efficacy and safety compared to TEE for LAAO.